2014
DOI: 10.1128/jvi.01108-14
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominance Changes as a Function of the Infecting Dengue Virus Serotype and Primary versus Secondary Infection

Abstract: Dengue virus (DENV) is the causative agent of dengue fever (DF). This disease can be caused by any of four DENV serotypes (DENV1 to -4) which share 67 to 75% sequence homology with one another. The effect of subsequent infections with different serotypes on the T cell repertoire is not fully understood. We utilized mice transgenic for human leukocyte antigens (HLA) lacking the alpha/beta interferon (IFN-␣/␤) receptor to study responses to heterologous DENV infection. First, we defined the primary T cell respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
97
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 47 publications
7
97
1
Order By: Relevance
“…Likewise, we did not see a difference in magnitude and breadth between these two groups. We have previously shown in a mouse model of DENV infection that secondary infection with the same serotype did not change the repertoire toward conserved epitopes, supporting this observation (20). We observed that after tetravalent vaccination the induction of responses predominantly targeting the nonstructural proteins NS3 and NS5, which are also preferentially targeted in natural DENV infection (9,21,22).…”
Section: Discussionsupporting
confidence: 71%
“…Likewise, we did not see a difference in magnitude and breadth between these two groups. We have previously shown in a mouse model of DENV infection that secondary infection with the same serotype did not change the repertoire toward conserved epitopes, supporting this observation (20). We observed that after tetravalent vaccination the induction of responses predominantly targeting the nonstructural proteins NS3 and NS5, which are also preferentially targeted in natural DENV infection (9,21,22).…”
Section: Discussionsupporting
confidence: 71%
“…Although testing these postulates is highly relevant to understanding both protective and 300 detrimental immune responses in dengue, only a few studies have compared immune responses during 301 or after primary versus secondary DENV infections. Consistent with the predictions, differences have 302 been reported in the expression of some phenotypic markers [71], in the dominant epitopes targeted 303 [78], and in the profile of serotype cross-reactivity [52,82]. Surprisingly, no significant differences were 304 observed in the kinetics of the response or in the peak T cell frequencies during the acute infection [48, 305 52].…”
Section: Artifact 130supporting
confidence: 67%
“…This is a particular problem in individuals who have been exposed to more than one 259 DENV serotype, either through sequential exposure or multivalent immunization. Although one study 260 concluded that serotype-specific epitopes could be defined based on sequence conservation alone [78], 261 other experimental data are directly contradictory [36, 37, 41]. Another study described a panel of CD4 262…”
Section: Artifact 130mentioning
confidence: 99%
“…We previously found that 80% homology is required for cross-reactivity at the level of DENV CD8 ϩ responses; the data suggest that cross-reactivity of DENV epitopes is far more extensive for CD4 ϩ than for CD8 ϩ responses (28). Secondary T cell responses to conserved/cross-reactive regions may contribute to the heightened protection and lower disease severity observed for tertiary heterotypic DENV infections (6,29) and may thereby represent a desirable attribute of vaccine-induced cellular responses.…”
Section: Discussionmentioning
confidence: 99%